Removals of Gentamicin and Benzo[a]Pyrene in an Anaerobic Multichamber Bed Reactor - Delia Teresa Sponza; Hakan Celebi; Oguzhan Gok (The Global Environmental Engineers, 2019)
The petrochemical industry wastewaters were not treated effectively due to high concentrations of Polycyclic aromatic hydrocarbon (PAH) benzo [a] pyren (BaP) and an aminoglucoside antibiotic gentamicin (GNT) in an aerobic treatment plant in Turkey. The high GNT concentration in this industry wastewater mainly originated from the toilets of the working people and from the medical care facilities since an intestinal epidemic occurrred for a period of approximately 1.5 years. The High BaP concentrations release into the wastewater originated from the high BaP production in this industry. In order to improve the biodegradability of petrochemical industry wastewaters containing excess BaP and GNT, different mixtures of BaP and GNT were biodegraded in a high rate anaerobic multichamber bed (AMCBR) reactor. The maximum anaerobic yields for 10 mg/L BaP and 1 mg/ L GNT alone were 45% and 12%, respectively. The addition of primary susbstrate increased the 200 mg/L BaP and 50 mg/ L GNT removals to 97% and 89%, respectively. BaP was biodegraded at short operation times compared to GNT. At low BaP (10-200 mg/ L) and GNT (10-35 mg/ L) concentrations, a non-competitive inhibition does not affect the binding of the substrate and KS were not affected. At high BaP (500-900 mg/ L) and GNT (75-100 mg/ L) concentrations, the BaP and GNT were biodegraded according to competitive inhibition with increased KS. BaP and GNT were biodegraded according to Haldane equations at high concentrations where they were used as the sole substrate.